Penerapan Komunikasi Efektif Dan Keluarga Terhadap Pencegahan Speech Delay Pada Balita Di Desa Bangun Rejo Kecamatan Tanjung Morawa Kabupaten Deli Serdang Provinsi Sumatera Utara Tahun 2024 - Nopalina Suyanti Damanik; Parningotan Simanjuntak; Yesica Geovani Sianipar; Ribur Sinaga; Maulidya Khairani; Isa Bella Simanjuntak (Compromise Journal Community Proffesional Service Journal, 2024)
Background Development of growth and development can be done by providing stimulation and early detection of the baby's growth and development during the "golden age" by providing adequate early stimulation to stimulate the brain and development of movement, speech and language as well as socialization and independence of the baby so that it is optimal according to its age.( Uli, 2019. The aim of this community service program (PKM) is to increase the implementation of effective and family communication towards preventing speech delay in toddlers in Bangun Rejo Village, Tanjung Morawa District, Deli Serdang Regency, North Sumatra Province in 2024. The methods used include 1) identifying toddlers about Speech Delay); 2) preparation of materials and steps for implementing effective and family communication towards preventing speech delay in toddlers); 3) implementation of education on the Implementation of Effective Communication and Family towards Prevention of Speech Delay in Toddlers). Results Based on the results of implementing community service for toddlers in Bangun Rejo Village, Tanjung Morawa District, Deli Serdang Regency, North Sumatra Province, there are a total of 19 toddlers, where the majority are 1-3 years old, 10 toddlers (53%), 3-5 years old, 9 toddlers (43%). %), all parents are enthusiastic about implementing effective and family communication towards preventing speech delay in toddlers